The antimicrobial action of resveratrol against Listeria monocytogenes in food-based models and its antibiofilm properties - Ferreira, Susana (2020)
Submitted by (smpf@ubi.pt) on 2020-01-29T13:20:30Z No. of bitstreams: 1 2016. The antimicrobial action of resveratrol against Listeria monocytogenes in food-based models and its antibiofilm properties.pdf: 538280 bytes, checksum: e93eebd7a80159b256d9a03c9cbfbf28 (MD5)